Depicting the role of cross‐cultural legitimacy for responsible innovation in Asian‐Pacific business models: A dialectical systems view of Yin‐Yang harmony. (9th May 2022) - Chin, Tachia; Caputo, Francesco; Shi, Yi; Calabrese, Mario; Aouina‐Mejri, Chiraz; Papa, Armando
Abstract: Recognizing the key role of innovation in ensuring the definition of managerial and organizational model able to support companies in facing the multiple challenges of sustainable development, the paper focuses on the domain of Responsible innovation (RI) with the aim to depict the role of cross‐cultural legitimacy for RI in Asian‐Pacific business models. Adopting the interpretative lens provided by Dialectical Systems View, the Yin‐Yang dichotomy is discussed for depicting the relationships among focal firms and stakeholders within in Asian‐Pacific cross‐cultural models. Hypotheses are tested via constructed stepwise regression models using secondary data related to a sample of large Chinese MNEs listed in the Shanghai and Shenzhen stock exchanges over the period from 2009 to 2018. The research shows the multiple influences that cultural legitimacy has in influencing RI and firm performance in the Asian‐Pacific cross‐cultural business models. Thanks to the study, the current debate about the role of innovation in supporting the definition of sustainable‐based business models is enriched through the definition of cross‐cultural legitimacy as key driver for RI in Asian‐Pacific business models. Thanks to the reflections herein, RI is definitely approached as a holistic domain whose understanding requires to researchers and practioners to overcome traditional business "boundaries."